2015
DOI: 10.1016/j.bse.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny, diversity, symbiosis and discover of bioactive compounds of endophytic fungi associated with the medicinal Amazonian plant Carapa guianensis Aublet ( Meliaceae )

Abstract: a b s t r a c tWe investigated the endophytic fungal community associated with the Amazonian medicinal plant Carapa guianensis and its potential for providing bioactive compounds. A total of 162 endophytic fungal isolates were obtained and identified by molecular methods. These isolates were classified into 35 different taxa in the genera Aspergilllus, Beltrania, Botryosphaeria, Colletotrichum, Diaporthe, Endomelanconiopsis, Fusarium, Guignardia, Pestalotiopsis, Phomopsis, Pilidiella, Trichoderma, and Xylaria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 32 publications
3
30
0
3
Order By: Relevance
“…Other studies showed leaves with the highest colonization of endophytic fungi (Souza et al, 2004). Similar to the results obtained in this study, Phomopsis and Pestalotiopsis were also one of the most frequent genera isolated as endophytic (Hilarino et al, 2011;Ferreira et al, 2015). Some fungal genera exhibited specificity in relation to the culture medium of isolation.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies showed leaves with the highest colonization of endophytic fungi (Souza et al, 2004). Similar to the results obtained in this study, Phomopsis and Pestalotiopsis were also one of the most frequent genera isolated as endophytic (Hilarino et al, 2011;Ferreira et al, 2015). Some fungal genera exhibited specificity in relation to the culture medium of isolation.…”
Section: Discussionsupporting
confidence: 88%
“…However, knowledge of the diversity of endophytic fungi, particularly in tropical forests, is incipient (Ferreira et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Colletotrichum isolated as endophytic fungus also showed antibacterial activity against gram-positive, gramnegative, and Candida albicans bacteria (Katoch et al, 2014;Ferreira et al, 2015).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Asterosporium and Aureobasidium were isolated only at 18°C, while Guignardia, Aspergillus, Botrytis, and Didymostilbe only at 28°C. Studies on endophytic fungi generally use temperatures between 25 and 28°C (Premalatha and Kalra, 2013;Campos et al, 2015;Ferreira et al, 2015).…”
Section: Isolation and Identification Of Endophytic Fungimentioning
confidence: 99%